2020
DOI: 10.1021/acs.jafc.0c04064
|View full text |Cite
|
Sign up to set email alerts
|

Ovotransferrin Exhibits Osteogenic Activity Partially via Low-Density Lipoprotein Receptor-Related Protein 1 (LRP1) Activation in MC3T3-E1 Cells

Abstract: Ovotransferrin, a major protein in egg white, induces osteoblast proliferation and survival in vitro. However, it is unclear which receptor(s) drive the beneficial activities of this bioactive glycoprotein. We examined the role of the low-density lipoprotein receptor-related protein 1 (LRP1) in the actions of ovotransferrin on osteoblasts. Here, we showed that LRP1 in part regulates osteogenic action of ovotransferrin. Mouse osteoblasts, MC3T3-E1, with LRP1 deletion displayed diminished osteogenic activity. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Both IGF-1 and ASPN have been reported to be involved in the process of osteoblast differentiation or collagen biomineralization. 60 , 61 We observed the co-localization of IGF-1 and ASPN with NF-1 and similar expression trends ( Figure 4 I and S8 F). The consistent results from the IF co-localization assay and in vitro cell differentiation assay also fortify the findings acquired from scRNA-seq data ( Figures S8 A and S8B).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Both IGF-1 and ASPN have been reported to be involved in the process of osteoblast differentiation or collagen biomineralization. 60 , 61 We observed the co-localization of IGF-1 and ASPN with NF-1 and similar expression trends ( Figure 4 I and S8 F). The consistent results from the IF co-localization assay and in vitro cell differentiation assay also fortify the findings acquired from scRNA-seq data ( Figures S8 A and S8B).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have proved that both LRP1 and ATF4 regulate the process of osteogenesis. 60 , 61 ATF4, a transcription factor, is able to promote biomineralization via mTOR signaling. 61 We observed the co-localization of FOBS and its targets (LRP1 and ATF4) ( Figures S7 A and S7B).…”
Section: Discussionmentioning
confidence: 99%
“…We performed RT-PCR using Fast SYBR Green PCR Master Mix (Applied Biosystem, Burlington, ON, Canada) and the amplification conditions were as follows: initial denaturation at 95 °C for 10 min followed by 35 cycles of 10 s at 95 °C, 15 s at 60 °C, and 10 s at 72 °C. as described in detail previously 52 . The primers used were PGC1α (FP: AGC CTC TTT GCC CAG ATC TT RP: GGC AAT CCG TCT TCA TCC AC), NRF1 (FP: CGG TAT GCA ACA GGA CAT TG RP: ACT GGT TGG GGT CTT CTG TG), ND1 (FP: ATC AGG GTG AGC ATC AAA RP: TTC GGT TGG TCT CTG CTA ), ND6 (FP: ACA GCA CCA ATC CTA CCT RP: ATT GTT AGC GGT GTG GTC ), ATP8 (FP: CCA CTG TAA AGC TAA CTT AGC RP: GTT AGG GGT CAT GGG CTG ) and GAPDH (FP: GAA GGT GAA GGT CGG AGT C RP: GAA GAT GGT GAT GGG ATT TC).…”
Section: Discussionmentioning
confidence: 99%
“…Shang (2019) reported that egg white ovotransferrin is responsible for enhancing the expression of type I collagen and alkaline phosphate, inhibition of the production of receptor activator of nuclear factor kappa-B (RANKL). (Shang et al, 2020) reported that the supplementation of ovotransferrin regulated the expression of genes that are involved in lipid metabolism, signal transduction, and the endocrine system, and showed that lipoprotein receptor-related protein 1 worked as a scavenger receptor and regulated the ability of ovotransferrin to promote bone formation. Ovotransferrin increased the beneficial microbiota population such as Akkermansia and affected mucosal morphology by increasing crypt depth.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%